Osmotic energy, a little-known renewable energy source (2016)
When the rivers lead into the sea, it merges two water bodies with different salinity level, releasing a large amount of energy when the solutions equilibrate its concentrations; this phenomenon is known as osmosis. With the purpose to use this energy to transform it into electricity, it has been developed a device with a semi-permeable membrane, when is placed between the solutions with different saline concentration, allows to equalize the concentration at a constant pressure or volume. The membrane behavior on the device is similar to the behavior of the living being cells membrane, that's the reason to call the device as a membrane module. Using a membrane module array is possible to get brackish water, with a pressure corresponding to the osmotic pressure that represents hydraulic energy that could be transformed into electricity by well-known means. This work presents a conceptual methodology for preliminary design of an osmotic power plant, which could be a theoretical reference for different alternatives to generate electricity in the places where it's possible to implement it, as the way to dimension and design the system, including concepts and parameters related to conventional, energy-production processes, allowing to know different methods for energy production that someday could be competitive with the traditional energy generation. © 2016 WIT Press.